The Effect of Magnesium on Reperfusion Arrhythmias in STEMI Patients, Treated With PPCI. A Systematic Review With a Meta-Analysis and Trial Sequential Analysis - Szapary, Laszlo B.; Szakacs, Zsolt; Farkas, Nelli; Schonfeld, Kristof; Babocsay, Dora; Gajer, Mate; Kittka, Balint; Magyari, Balazs; Hegyi, Peter; Szokodi, Istvan; Horvath, Ivan G. (Frontiers in Cardiovascular Medicine, 2021)
The restoration of coronary circulation plays a crucial role in treating ST-segment elevation myocardial infarction (STEMI), however successful reperfusion with primary percutaneous coronary intervention (PPCI) may induce life-threatening arrhythmias. The relation between myocardial electrical instability, as a background factor in reperfusion arrhythmia, and magnesium administered periprocedurally is still questionable. Due to the contradictory results of the previous studies, there is little evidence of the potential preventive effect of magnesium on reperfusion arrhythmias. The aim of our study is to review and meta-analytically analyze data from all studies published so far in the PPCI era, comparing STEMI patients who have undergone primary PCI and received either magnesium or a placebo before the reperfusion procedure. We conducted a search in five scientific databases using the following keyword combination: (myocardial infarction OR myocardial injury OR acute coronary syndrome OR acs OR stemi) AND magnesium). A statistical analysis was performed on three randomized-controlled trials using three common parameters, involving 336 patients Trial sequential analysis (TSA) was applied to assess the risk of random error associated with sparse data and multiple testing which can affect cumulative meta-analysis. The incidence of ventricular tachycardias (VTs) was not significantly increased in the non-magnesium control group. (OR: 1.36; CI: 0.619; -2.986, P: 0.263). For the ejection fraction (EF), a non-significant decrease was observed in the magnesium group by weighted mean difference calculation. (WMD: 7.262, 95% CI: -0.238; 0.053; P: 0.057). There was significant decrease in the infarct zone wall motion index (IZWMSI) in the magnesium treatment group. (WMD: 0.384, 95% CI: -0.042; 0.811, P: 0.015) Based on the TSA assessments, the results of all parameters are not significant, objectively demonstrating the lack of reasonable data pertaining to our question. The preventive effect of magnesium on reperfusion arrhythmia associated with primary PCI can still be considered contradictory based on previous studies. In our study, we found, that magnesium is ineffective with weak evidence, due to the small number of patients and the biases of the included studies, and a well-designed clinical trial is needed in this area, based ont he TSA.